Determinants Customer Loyalty Price Perception Promotion and Service Quality - Ahfi Nova Ashriana (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2023)
The purpose of this study is to ascertain the impact of price perception, promotion, and service quality on customer loyalty at Sanrio Mojokerto supermarkets. This study is an example of a survey study. The people who shop at Sanrio Mojokerto supermarkets make up the study's demographic. A sample of 100 participants was acquired using the incidental sampling technique in this investigation. The questionnaire used for data collection has undergone validity and reliability testing. Multiple linear regression analysis is the data analysis method used to determine whether the research hypothesis is true. The findings demonstrated that consumer loyalty at Supermarkets Sanrio Mojokerto was positively and significantly impacted by price perceptions, promotion, and service quality.